Contro la “giustizia bianca”. La relazione tortuosa tra schiavitù, razza e diritto (Stato, Chiese e pluralismo confessionale, 2024)
Against a “white justice”. The tortuous relation between slavery, race and lawABSTRACT: The present article aims to analyze slavery as a specific and global phenomenon, meaning it as a condition of subordination of one man to another man. I will analyze the pro-slavery and anti-slavery arguments, the Critical Race Theory’s reflections about the relationship between law and racism, and eventually I will focus on current forms of slavery.SOMMARIO: 1. Introduzione - 2. Un percorso storico e giusfilosofico: le argomentazioni a favore della schiavitù ... - 3. (segue) ... e le argomentazioni contrarie alla schiavitù - 4. Disuguaglianza, diritti e razza: la prospettiva della Critical Race Theory - 5. La schiavitù esiste ancora? La tratta di esseri umani - 6. Considerazioni conclusive.